Five-circuit electric bridge and its properties - Лебедев, Павел Федорович; Дробышева, Вита Петровна; Токарь, Екатерина Петровна (Eastern-European Journal of Enterprise Technologies, 2014)
The modern theory of electric bridges is based on improving two structures, related to the Wheatstone and Thompson bridges. The structure remains unchanged, and individual branches are subject to the development. The discovery of the law on dual structures allows to expand the technical capabilities of bridges. The paper considers only the "bridge effect" and some of the mentioned properties, typical for resistive circuits and circuits with constant currents and voltages, for example, perfect five-circuit bridges. The following provisions are set. Five-circuit bridge can compete with the famous bridges in various kinds of measurements. It was found that the "bridge effect" can be achieved not only due to the correlation of the circuit parameters, but also the impact of sources. It is possible to use bridges in the power supply to save energy by eliminating the influence on each other. Frequency-independent bridge under harmonic effects can also provide independent operation modes of electrical power sources.